Ochrona zabytków na wypadek sytuacji kryzysowej - Kocowska-Siekierka, Elżbieta (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article presents the regulation of heritage protection in the event of a crisis situation in Poland. It presents the most important legislation in the field of general security, as well as in the protection of museum collections and religious monuments. It presents the most important provisions relating to the responsibilities of guardians of monuments which is the creation of the monument protection plans in the event of armed conflict and crisis situations.
Keywords: ochrona zabytków; sytuacja kryzysowa; ochrona muzealiów; ochrona zabytków sakralnych; ochrona międzynarodowa